Optimization Strategies for Student Scientific Publications in Islamic Higher Education Institutions to Enhance Academic Competence Based on Outcome-Based Education (OBE) - Al Hadi, Abil Fida Muhammad Qois; Anggraini , Fadhilla Nangroe Anggraini; Asmara, Linda; Murni, Latifah Insani Muslimah; Salim, Muhammad Fathi (Universitas Muhammadiyah Surakarta, 2025)
Higher education demands that students not only master knowledge but also actualize their ideas through scientific works, including journal article publications. However, low literacy interest, lack of writing skills, and limited understanding of the publication process present major student challenges. This study aims to examine and develop innovative strategies to enhance students' scientific writing skills as an alternative to thesis writing to support the achievement of the Tri Dharma of Higher Education, particularly in accredited scientific publications. This research uses a qualitative approach with a phenomenological method, conducted through interviews, observations, and documentation. Data analysis was done through data reduction, data presentation, and conclusion drawing, employing triangulation of techniques and sources. The results show that journal publication plays a strategic role in shaping students' academic culture. However, challenges such as low literacy, lack of mentoring, and low motivation remain significant barriers. Study programs have implemented writing workshops, intensive mentoring, incentive provision, and hands-on writing practice to encourage student productivity. It can be concluded that strategies based on active practice, lecturer-student collaboration, and support through facilities and incentives effectively improve the quality of students' journal publications. The implementation of these strategies not only improves students' writing skills but also strengthens a productive and collaborative academic culture within higher education institutions. Furthermore, this approach accelerates the achievement of the Tri Dharma of Higher Education, particularly in research and scientific publications.